Fish Diversity of the Meghna River Adjacent to Sonargaon Upazila of Narayanganj District (Bangladesh Journal of Zoology, 2022)
The study was conducted to assess the diversity of fish fauna in the Meghna River close to Sonargaon upazila, Narayanganj district between December 2017 and November 2018. Some water quality parameters (temperature, pH and transparency) were measured in two selected sites (Boidyerbazar ghat and Uddamganj) of the river. In this study, a total of 58 fish species were identified, which belong to nine orders, 26 families and 41 genera. Cypriniformes was the most dominant order contributing about 34.48% of the fish species diversity. A total of 30 species were considered as of Least Concern (LC) while ten species were Near Threatened (NT), seven species were Endangered (EN), six species were Vulnerable (VU), only one species Bagarius bagarius ranked as Critically Endangered (CE) and four species were not listed according to IUCN (2015). The highest number of fish species was observed in the rainy season while the lowest was in the summer. The ranges of water temperature, pH and turbidity values in the river were 21-32 C, 6.5-8.5 and 23-42 NTU, respectively. This study indicates that the fish species diversity of the Meghna River is likely declined gradually when compared with previous studies.Bangladesh J. Zool. 50 (1): 23-35, 2022